Longitudinal Evaluation of Bronchial Changes in Cystic Fibrosis Patients Undergoing Elexacaftor/Tezacaftor/Ivacaftor Therapy Using Lung MRI With Ultrashort Echo‐Times - David, Mathieu; Benlala, Ilyes; Bui, Stephanie; Benkert, Thomas; Berger, Patrick; Laurent, François; Macey, Julie; Dournes, Gael (Journal of magnetic resonance imaging, 2024)
Background Lung magnetic resonance imaging (MRI) with ultrashort echo‐times (UTE‐MRI) allows high‐resolution and radiation‐free imaging of the lung structure in cystic fibrosis (CF). In addition, the combination of elexacaftor/tezacaftor/ivacaftor (ETI) has improved CF clinical outcomes such as need for hospitalization. However, the effect on structural disease still needs longitudinal evaluation at high resolution. Purpose To analyze the effects of ETI on lung structural alterations using UTE‐MRI, with a focus on bronchiectasis reversibility. Study Type Retrospective. Population Fifty CF patients (mean age 24.3 ± 9.2; 23 males). Field Strength/Sequence 1.5 T, UTE‐MRI. Assessment All subjects completed both UTE‐MRI and pulmonary function tests (PFTs) during two annual visits (M0 and M12), and 30 of them completed a CT scan. They initiated ETI treatment after M0 within a maximum of 3 months from the annual examinations. Three observers scored a clinical MRI Bhalla score on UTE‐MRI. Bronchiectasis reversibility was defined as a reduction in both outer and inner bronchial dimensions. Correlations were searched between the Bhalla score and PFT such as the forced expiratory volume in 1 second percentage predicted (FEV1%p). Statistical Tests Comparison was assessed using the paired t‐test, correlation using the Spearman correlation test with a significance level of 0.05. Concordance and reproducibility were assessed using intraclass correlation coefficient (ICC). Results There was a significant improvement in MRI Bhalla score after ETI treatment. UTE‐MRI demonstrated bronchiectasis reversibility in a subgroup of 18 out of 50 CF patients (36%). These patients with bronchiectasis reversibility were significantly younger, with lower severity of wall thickening but no difference in mucus plugging extent (P = 0.39) was found. The reproducibility of UTE‐MRI evaluations was excellent (ICC ≥ 0.95), was concordant with CT scan (N = 30; ICC ≥ 0.90) and significantly correlated to FEV1% at PFT at M0 (N = 50; r = 0.71) and M12 (N = 50; r = 0.72). Data Conclusion UTE‐MRI is a reproducible tool for the longitudinal follow‐up of CF patients, allowing to quantify the response to ETI and demonstrating the reversibility of some structural alterations such as bronchiectasis in a substantial fraction of this study population. Level of Evidence 4 Technical Efficacy Stage 2